Apparent permeability in tight gas reservoirs combining rarefied gas flow in a microtube - Zheng, Lingli; Chen, Muyao; Li, Tao; He, Jiahuan; Li, Yongming; Xiao, Wenlian (Frontiers in Earth Science, 2023)
In tight gas reservoirs, the major flow channels are composed of micro/nanopores, in which the rarefaction effect is prominent, and the traditional Darcy law is not appropriate for gas flow. Combining the Maxwell first-order slip boundary condition and Navier-Stokes equations, a three-dimensional (3D) analysis of compressible gas slip flow in a microtube was presented, and the flux rate and pressure variation in the flow direction were discussed. Subsequently, by superimposing the Knudsen diffusion, a gas flux formula applicable to a larger Knudsen number was further proposed and satisfactorily verified by two groups of published experimental data in microtubes or microchannels in the membrane. The results indicate that slip flow and Knudsen diffusion make an important contribution to the total gas flow in the microtube, and their weight increases with an increase in the Knudsen number. By substituting the gas flux formula into Darcy’s law for compressible gas, a new apparent permeability model for tight gas reservoirs was proposed, in which the slippage effect and Knudsen diffusion were synthetically considered. The results indicate that the apparent permeability of tight reservoirs is strongly dependent on the reservoir pressure and pore-throat radius, and an underestimation value may be predicted by previously published models. This study provides a case study for evaluating these apparent permeability models, which remains a challenging task in the laboratory.